Analisis Suprasegmental Penutur Laki-Laki dan Perempuan pada Kalimat Imperatif Bahasa Batak Toba - Parasian, Nehemia Anugrah; Adipati, M Yus; Syarfina, Tengku; Erwina, Emmy (Universitas Lampung, 2025)
Suprasegmentals are language sounds that accompany phonemes, which can be in the form of sound pressure, length-shortness, and sound vibrations associated with speech segments. Suprasegmentals in this study includes the frequency, intensity, and duration of the sounds produced. This study aims to analyze the differences in frequency, intensity, and duration of the sounds produced by male and female speakers in pronouncing Toba Batak imperative sentences, namely: “beta hita tu topi tao!” which means ‘let's go to the lakeside!’. This research method uses an instrumental approach by maximizing Praat software in analyzing frequency, intensity, and duration. The population and sample taken in this study is the voice of one native male and female speaker. The results of the analysis of this study show, namely: (1) the frequency of male speakers' voices is lower than female speakers; (2) the intensity of male speakers' voices is smaller than female speakers; and (3) the duration of male speakers' voices takes longer than female speakers to say the sentence. From this research, it can be seen that male and female voice differences have relevance to suprasegmental because both focus on the nonsegmental aspects of language, which play an important role in verbal communication.Keywords: suprasegmentals, frequency, duration, intensity